2014
DOI: 10.1016/j.jsat.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Leaving buprenorphine treatment: Patients' reasons for cessation of care

Abstract: Many opioid-dependent patients leave treatment prematurely. This study is a planned secondary analysis from a randomized trial of counseling for African Americans (N=297) entering buprenorphine treatment at one of two outpatient programs. This study examines: (1) whether patients’ initial treatment duration intentions prospectively predict retention; and (2) patients’ reasons for leaving treatment. Participants were queried about their treatment duration intentions at treatment entry, and their reasons for lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
97
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 30 publications
7
97
1
Order By: Relevance
“…Retention rates in treatment reported in the literature vary widely, but it is generally estimated that >50% of patients leave or are withdrawn in the first 3 weeks of treatment. [12][13][14] After 6 months of treatment, one study reported retention of 79%, [15] but others noted much lower rates of 58%, [16] 46% [17] and 27%. [18] In another study, an average of only 44% of buprenorphine clients spent at least 3 weeks in an Australian treatment facility.…”
Section: Discussionmentioning
confidence: 99%
“…Retention rates in treatment reported in the literature vary widely, but it is generally estimated that >50% of patients leave or are withdrawn in the first 3 weeks of treatment. [12][13][14] After 6 months of treatment, one study reported retention of 79%, [15] but others noted much lower rates of 58%, [16] 46% [17] and 27%. [18] In another study, an average of only 44% of buprenorphine clients spent at least 3 weeks in an Australian treatment facility.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who perceive they have a low risk for opioid relapse demonstrate less interest in engaging in OMT (Bailey, Herman, & Stein, 2013) and express a shorter intended duration of treatment (Winstock, Lintzeris, & Lea, 2011). For those patients who do engage in OMT, dissatisfaction with program rules drives much of OMT discontinuation (Gryczynski et al, 2013; Reisinger et al, 2009) despite high levels of patient satisfaction with the OMT treatment itself (Barry et al, 2007; Ling, Hillhouse, Ang, Jenkins, & Fahey, 2013). Patient perspectives, such as these, may contribute to suboptimal treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only two reports have specifically addressed how patient perspectives of buprenorphine maintenance therapy (BMT) are associated with treatment duration (Gryczynski et al, 2013; Winstock et al, 2011). One report revealed that intended treatment duration was longer in patients who had been enrolled in BMT for a longer period of time and who were more concerned about relapse (Winstock et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations